THE QUIDDITY OF CERTITUDE (QAT) AND ITS IMPLICATIONS IN THE APPEARANCES AREA OF USUL AL-FIQH Ø¯ÙˆØ±Ù‡51 Ø´Ù…Ø§Ø±Ù‡4 Ø³Ø§Ù„1398 - ?????? ?????, ???? ????; ????? ????, ????; ???? ????, ????? ???? (??? ? ????)
The Usulis who came after Seikh Ansari, by dividing the duty-bound conditions into three, have discussed topics of authority in three fields of certitude (Qat), conjecture (Zann) and doubt (Shakk). Their selected opinion with regard to certitude has constituted their basics in the two other fields and affected them. One of the above said opinions concerns the quiddity of certitude. According to the viewpoint of some new Usulis, the appearance of a word denotes the speaker?s purpose and the origin of appearance is the usage intention. Accordingly, the appearance of a word in the mind of addressee or other hearer is realized thorough acknowledgement of the speaker?s purpose and its origin is rational principles. Considering these principles as rational leads to considering acknowledgment and denotation of appearance as definite. Considering denotation of appearances as definite has implications. For instance, the appearances by exiting the scope of al-Amarat al-Zanniya and entering the realm of definite proofs acquire inherent authority and exit by their nature the area of proofs which prohibit acting without knowledge. Therefore, it may be claimed that not only the authority of appearances is the requirement of the primary principle but also acting on the basis of appearances may not be deterred by the lawgiver.